Implementasi Stack dan Array pada Pengurutan Lagu dengan Metode Selection Sort - Putri, Ghina Mawarni; Pradja, Kimberly Alfa Di; Azizi, Muhammad Bilal Mardhiyyano; Nurwahid, Prihatma; Perdana, Abdi Surya; ., Munawir (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
A song is a work of art combined between sound art in which there is a melody and color of the singer's voice with language art. The number of songs nowadays requires a program that can sort songs to make it easier for users to find songs. This article aims to apply stack and array data structures to sort songs with the selection sort algorithm method in the hope that it can make it easier for users to find songs. In addition, this article aims to compare whether the selection sort algorithm is faster than insertion sort or vice versa. In making this journal, a literature study research method was carried out to deepen the material to be used in the project. The results of the program that has been made are that users can choose between adding songs, searching for songs, displaying songs that are already in the list, sorting songs, and exiting the program. With this, users can access and add their favorite songs anywhere and anytime. The conclusion of the results obtained is that selection sort is faster than insertion sort.